Impact of cardiac amyloidosis on outcomes of patients hospitalized with heart failure - Göbel, Sebastian; Hobohm, Lukas; Desuki, Alexander; Gori, Tommaso; Münzel, Thomas; Claudio, Rapezzi; Wenzel, Philip; Keller, Karsten (European journal of internal medicine, 2022)
Background - Amyloidosis is a multi-systemic disease potentially leading to failure of affected organs. We aimed to investigate prevalence and prognostic implications of cardiac amyloidosis of any etiology on outcomes of hospitalized patients with heart failure (HF) in Germany. - Methods - We analyzed data of the German nationwide inpatient sample (2005-2018) of patients hospitalized for HF (including myocarditis with HF and heart transplantation with HF). HF patients with amyloidosis (defined as cardiac amyloidosis [CA]) were compared with those HF patients without amyloidosis and impact of CA on outcomes was assessed. - Results - During this fourteen-year observational period 5,478,835 hospitalizations for HF were analyzed. Amyloidosis was coded in 5,407 HF patients (0.1%). CA prevalence was 1.87 hospitalizations per 100,000 German population. CA patients were younger (75.0[IQR 67.0-80.0]vs.79.0[72.0-85.0]years, p < 0.001), predominantly male (68.9%) and had a higher prevalence of cancer (14.8% vs. 3.6%, p < 0.001). Adverse in-hospital events including necessity of transfusions of blood constituents (7.1% vs. 5.4%, p < 0.001) and cardio-pulmonary resuscitation (CPR, 2.7% vs. 1.4%; p < 0.001) were more frequent in CA. CA was independently associated with acute kidney failure (OR 1.40 [95%CI 1.28-1.52], p < 0.001), CPR (OR 1.58 [95%CI 1.34-1.86], p < 0.001), intracerebral bleeding (OR 3.13 [95%CI 1.68-5.83], p < 0.001) and in-hospital mortality between the 5 and 8th decade of life, but in-hospital mortality was strongly influenced by cancer. - Conclusions - CA was identified as an independent risk factor for complications and in-hospital mortality in HF patients, whereby it has to be mentioned that amyloidosis subtypes could not differentiated in the present study. Physicians should be aware of this issue concerning treatments and monitoring of CA-patients.